Socio-demographic determinants of morbidities in infancy: a cross sectional study in urban field practice area of MRMC, Kalaburagi - Naaz, Faraha; Nigudgi, S. R.; Ghooli, Shreeshail (International Journal Of Community Medicine And Public Health, 2018)
Background: The first few years of life is the most crucial period of life as this age is known for accelerated growth and development. Various studies in India have shown that respiratory and gastrointestinal tract infections are the leading cause of morbidity in infants. These infectious diseases are affected by several sociodemographic factors such as birth weight, gestational age, birth order, immunization status, day care attendance and socio-economic status of the family. Methods: A cross sectional study was conducted in the urban field practice area of department of community medicine MRMC, Kalaburagi from June 2016-October 2016. House to house survey using pre-structured and pretested questionnaire method was done. Results: Out of 104 infants in the present study it was found that majority 53% were females and 49% were males. Majority 61.5% of the infants belonged to low socioeconomic class and majority 54.8% of them were from nuclear families, most 62.5% of the infants had 1-2 siblings in the family and 34.6% had no siblings, 51% of the mothers were illiterate and majority 54.8% of the fathers were literate. Among all the morbidities majority 36.50% had fever. No significant association was found between various social factors. Conclusions: Though no significant association was found between morbidity and socio-demographic factors, but the socio demographic factors which showed more prevalence of morbidity among infants were females, number of siblings in the family and lower socio economic class. As these infants are the future citizens of the country hence their health should be the utmost priority for us and their health needs should be properly addressed.